In Vitro Induction of Tendon-Specific Markers in Tendon Cells, Adipose- and Bone Marrow-Derived Stem Cells is Dependent on TGF3, BMP-12 and Ascorbic Acid Stimulation - Perucca Orfei, Carlotta; Viganò, Marco; Pearson, John R.; Colombini, A.; De Luca, P.; Ragni, E.; Santos-Ruiz, Leonor; De Girolamo, Laura (MDPI, 2019)
Mesenchymal Stem Cells (MSCs) and tissue-specific progenitors have been proposed as useful tools for regenerative medicine approaches in bone, cartilage and tendon-related pathologies. The differentiation of cells towards the desired, target tissue-specific lineage has demonstrated advantages in the application of cell therapies and tissue engineering. Unlike osteogenic and chondrogenic differentiation, there is no consensus on the best tenogenic induction protocol. Many growth factors have been proposed for this purpose, including BMP-12, b-FGF, TGF-3, CTGF, IGF-1 and ascorbic acid (AA). In this study, different combinations of these growth factors have been tested in the context of a two-step differentiation protocol, in order to define their contribution to the induction and maintenance of tendon marker expression in adipose tissue and bone marrow derived MSCs and tendon cells (TCs), respectively. Our results demonstrate that TGF-3 is the main inducer of scleraxis, an early expressed tendon marker, while at the same time inhibiting tendon markers normally expressed later, such as decorin. In contrast, we find that decorin is induced by BMP-12, b-FGF and AA. Our results provide new insights into the effect of different factors on the tenogenic induction of MSCs and TCs, highlighting the importance of differential timing in TGF-3 stimulation.
Keywords: Células madre; Tenogenic differentiation; Mesenchymal Stem Cells (MSCs); Adipose-derived MSCs; Bone marrow-derived MSCs; Tendon cells; BMP-12; FGF; TGFbeta; Ascorbic acid; SCLERAXIS; DECORIN